2015
DOI: 10.1053/j.ajkd.2014.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Arterial Microcalcification and Clinical Outcomes of Arteriovenous Fistulas for Hemodialysis

Abstract: Background Arteriovenous fistulas (AVFs) often fail to mature, but the mechanism of AVF non-maturation is poorly understood. Arterial micro-calcification is common in patients with chronic kidney disease (CKD), and may limit vascular dilatation, thereby contributing to early postoperative juxta-anastomotic AVF stenosis and impaired AVF maturation. This study evaluated whether preexisting arterial micro-calcification adversely affects AVF outcomes. Study Design Prospective study. Setting & Participants 127 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 25 publications
2
39
0
Order By: Relevance
“…In contrast, using histologic analysis, preexisting microcalcification in arteries used for AVF creation did not predict postoperative stenosis, AVF maturation, or primary unassisted patency (38,50). Arterial macrocalcification, as determined by preoperative ultrasound, correlated well with arterial microcalcification and was also not associated with AVF nonmaturation (50). This study, however, excluded patients with severe concentric calcification, which is better detected by plain radiographs.…”
Section: Vascular Calcification and Avf Outcomesmentioning
confidence: 75%
See 1 more Smart Citation
“…In contrast, using histologic analysis, preexisting microcalcification in arteries used for AVF creation did not predict postoperative stenosis, AVF maturation, or primary unassisted patency (38,50). Arterial macrocalcification, as determined by preoperative ultrasound, correlated well with arterial microcalcification and was also not associated with AVF nonmaturation (50). This study, however, excluded patients with severe concentric calcification, which is better detected by plain radiographs.…”
Section: Vascular Calcification and Avf Outcomesmentioning
confidence: 75%
“…Calcification severity in patients on hemodialysis with working AVFs as determined by radiology correlated with worse AVF patency in a 5-year follow-up study (49). In contrast, using histologic analysis, preexisting microcalcification in arteries used for AVF creation did not predict postoperative stenosis, AVF maturation, or primary unassisted patency (38,50). Arterial macrocalcification, as determined by preoperative ultrasound, correlated well with arterial microcalcification and was also not associated with AVF nonmaturation (50).…”
Section: Vascular Calcification and Avf Outcomesmentioning
confidence: 98%
“…However, data from the Hemodialysis Fistula Maturation Study reveal that noncompliant feeding arteries are associated with a lower incidence of early thrombosis (57). Arterial microcalcification itself may not be associated with maturation failure (62,63) if the artery is of adequate size and overall quality to allow for surgical proximal and distal control and suture placement.…”
Section: Arterial Size/qualitymentioning
confidence: 99%
“…While Choi et al [2] found an association between pre-existing arterial microcalcification of the vascular access and AVF failure, Allon et al [3] reported that neither AVF nor arteriovenous graft survival was associated significantly with vascular microcalcification. Our results, although obtained by examination of a small group of patients, are in agreement with the latter, indicating no association between arterial microcalcification and AVF failure.…”
Section: To the Editormentioning
confidence: 98%